Producing New Affective Concepts of Race in an English Classroom. Issue 1 (2nd January 2022) - Sosa, Teresa
ABSTRACT: Focusing on moments in the English classroom imbued with affective forces that produce racial differentiation is central to the support of classrooms addressing race and racism. This work focuses on an event in an English classroom where race was constructed in ways that disrupted not only silence but habitual ways of social differentiation. Through an analysis of two student's responses to an image of Basquiat, I make the case for how affect as a constellation of language, power, bodies, and historical, cultural, social and political norms and conventions informed each students' response. I also address how affective encounters can prime teachers for future discussions and activities that also/further disrupt ideologies of race.